EFFECT OF CARBONIC ACID ADDITIVES ON LUBRICANT LAYER IN THE LOCAL CONTACT OF GEAR TRANSMISSIONS - Кіндрачук, Мирослав; Мельник, Володимир; Леусенко, Дар`я (Problems of Friction and Wear, 2022)
A study was made of lubricating layers formed by oils with surface-active additives of carboxylic acids in the local contact of gears. The studies have established high running-in properties of such additives, which are due to both the adsorption plasticizing effect and the reduction in the thickness of the hydrodynamic layer. Excessive reduction in the thickness of the lubricating layer in the presence of surfactants can lead to direct contact of the bumps. In this case, protection against setting is provided by adsorption and oxide films. In particular, the formic acid additive obviously forms insufficiently effective adsorption films. At the same time, formic acid is a good reducing agent and is widely used in engineering as such. A decrease in the thickness of the oxide film with a small thickness of the viscous and adsorption layers is the reason for the development of setting.